2009
DOI: 10.1186/1742-4755-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity and reproductive health among Arabs

Abstract: Consanguineous marriages have been practiced since the early existence of modern humans. Until now consanguinity is widely practiced in several global communities with variable rates depending on religion, culture, and geography. Arab populations have a long tradition of consanguinity due to socio-cultural factors. Many Arab countries display some of the highest rates of consanguineous marriages in the world, and specifically first cousin marriages which may reach 25-30% of all marriages. In some countries lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
394
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(421 citation statements)
references
References 102 publications
21
394
3
3
Order By: Relevance
“…It is possible that educated men are considered an asset to the family because they may earn more and can support large families and accumulate assets and property, and hence, their commitment to marry a relative is greater. It has been shown that lower consanguinity rates were found among educated women but not among educated men (Tadmouri et al 2009). This is borne out by the finding in a 2004 report that 44.7 % of the Bedouin women in Israel completed only 6 years of schooling (Israel Center for Disease Control 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that educated men are considered an asset to the family because they may earn more and can support large families and accumulate assets and property, and hence, their commitment to marry a relative is greater. It has been shown that lower consanguinity rates were found among educated women but not among educated men (Tadmouri et al 2009). This is borne out by the finding in a 2004 report that 44.7 % of the Bedouin women in Israel completed only 6 years of schooling (Israel Center for Disease Control 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Middle East, Northern Africa, and South Asia are regions that have historically and culturally had a high rate of consanguineous unions (AlAwadi et al 1985;Al-Gazali et al 1997;Jaber et al 1997;Bittles et al 2002;Bener and Alali 2006). Recent studies have shown that 20 % to 50 % of marriages in Arab countries are between relatives (Tadmouri et al 2009;Bittles 2011;Hamamy et al 2011). The rate was 68 % in Egypt (Mokhtar and Abdel-Fattah 2001), 51-58 % in Jordan (Khoury and Massad 1992;Sueyoshi and Ohtsuka 2003;Hamamy et al 2005), 52 % in Qatar (Bener and Alali 2006;Bener and Hussain 2006), 50 % in the United Arab Emirates (Bener et al 1996), 54 % in Kuwait (Al-Awadi et al 1985;Hijazi and Haider 2001), 58 % in Saudi Arabia (El-Hazmi et al 1995), 40 % to 47 % in Yemen (Jurdi and Saxena 2003;Gunaid et al 2004), and 50 % in Oman (Rajab et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…3 RT-PCR/sequence analysis of the mutation (IVS3+5g>t) of patient 2 in which skipping of exon 3 of the CTNS gene is evident compared to a healthy individual cystinosis, which is different from many populations in which a single mutation may constitute over 50% of causative mutations. Also the high rate of homozygous mutations in our study (67%) sheds light on the gravity of the role of consanguineous marriage in elevating the incidence of nephropathic cystinosis and other autosomal recessive disorders in Egypt and in other Arab countries with similar and even higher rates of consanguineous marriages (Tadmouri et al 2009). The novel mutations found in this study include the frameshift mutation (c.260_261delTT; p.F87SfsX36) detected in patient 8, converting phenylalanine at position 87 to serine and resulting in a truncated protein at AA 123, completely abolishing the protein function.…”
Section: Discussionmentioning
confidence: 49%